Componente teórico para un modelo tutorial en práctica docente en estudiantes para profesor de matemáticas: reflexión desde la experiencia en contextos de aprender a enseñar - Guerrero R., Fernando (Revista Científica, 2011)
The model of return raised by Brousseau (1998) is explored in the educational practices of the Students for Professors of mathematics 3to reflect on and in the educational action in the classroom of mathematics. For it in the space of formation of the class of educational practice it is tried to generate knowledge in the action from the position of a guardian that carries out the professor of practice on the design and planning, management and evaluation of a didactic sequence around the understanding of mathematical concepts in the basic Education. The position of a guardian of the practice professor is assumed like a reflective practicumthrough the resolution of problems of the professor. The practice professor generates conditions so that in the space of formation of the position of a guardian, the epps learn to make decisions on the instructive process, this practical knowledge serves to them to support his own judgment on learning to teach.